PENGABDIAN MASYARAKAT DAN SURVEY INDEKS DMF-T DAN def-t PADA ANAK SEKOLAH DASAR NEGERI 07 MARGASARI, KECAMATAN MARGASARI, KABUPATEN TEGAL, JAWA TENGAH - Hadianto, Eko; Fathurrahman, Helmi; Mayangsari, Regilia Shinta; Yuniar, Savira Nurazky; Indrawati, Silvia Vera; Dimas P. P., Muhammad (Jurnal Pengabdian Masyarakat DentMas, 2023)
Background: Caries is a chronic disease of the dental hard tissue. The main cause of this disease is plaque bacteria, starting with the formation of white spot lesions due to the dissolving of minerals in tooth enamel caused by acids from the metabolism of bacterial carbohydrates. Caries often occurs in elementary school children because they tend to consume a lot of cariogenic food. The prevalence of caries can be reduced by preventive efforts. Several preventive efforts can be made by providing sufficient information, reducing cariogenic food consumption, always maintaining oral and dental hygiene and preventive dentistry actions. Method: This community service located at SD N Margasari 07. The counseling activity uses phantom and video animation followed by DMF-T/def-t data collection. Result: It was found that 41.8% of students had high category DMF-T/def-t index Conclusion: It is necessary to have a sustainable program to increase children's knowledge and awareness in maintaining dental and oral hygiene including promotive, preventive and curative efforts.